The Examination of Teacher Candidates’ Level of Proficiency in Technopedagogical Education (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The purpose of this study is to investigate preservice elementary mathematics teachers` techno pedagogical knowledge competencies and performance indicators defining these competencies. In this qualitative study, teaching practices which was prepared in learning domain such as numbers and operations, algebra, geometry and measurement, statistics and probability and with different dynamic mathematical software (GeoGebra, Cabri3D and Tinkerplots) by 24 prospective mathematics teachers’ candidates were investigated. Data of study was collected through video records and lesson plans filled out by the prospective teachers after their teaching sessions. Data were analyzed within executing the teaching process and problem solving competency fields of technopedagogical education. Findings indicate that technology is used as an explorative tool for the first time in teaching the subject, technology based activities are prepared  to prevent misconception; however, they were forced to use technology in assessment evaluation process.